Modifying state-of-art adsorbents for CO2 capture by amine incorporation and ion-exchange - Bezerra, Diôgo Pereira (2014)
CO2 is the major Greenhouse Gas (GHG), which may cause undesired consequences to the environment, such as global warming. There are many options for CO 2 separation, among which adsorption on porous materials is highlighted in this work. Activated c arbons and zeolites have been proposed as potential adsorbents due to their natural affinity for CO 2 and to the possibility of tailoring textural properties and surface chemistry to enhance capacity and selectivity under specific capture scenarios. This th esis focuses on changing the surface chemistry of conventional adsorbents, by means of amine impregnation and ion - exchange, so as to examine the effect of such modifications on their performance for CO 2 capture. The experimental section was divided into th ree distinct studies. Initially, CO 2 adsorpti on isotherms were obtained on X zeolite functionalized with increasing concentrations of 2 - aminoethanol ( monoethanolamine , abbreviated as MEA ) . Subsequently, activated carbon was investigated as a support for a min e impregnation for CO 2 capture. Lastl y, a study of ion exchange in X z eolite was conducted in order to investigate the influence of different compensation cations in CO 2 capture. In general, MEA impregnation led to a deterioration in the textural proper ties of the examined adsorbents, which are essentially microporous. It seems the amine s fill completely the micropores , as the concentration of impregnating solution increases. There is experimental evidence that part of the loaded amine covalently bonds t o the zeolitic framework. CO 2 adsorption capacity is always lower for MEA impregnated solids than for the pristine support at 298 K, but the same is not true at 348 K. X zeolite keeps texture and crystalline structure intact upon ion - exchange. CO 2 adsorpti on is enhanced for smaller and lighter compensating cations, such as Li , reaching 4.82 mmol/g at 348 K and 1 bar . In terms of working capacity (between 0. 1 and 1 bar) at 298 K, Ba exchanged X zeolite performs better than the other solids . It remains to be studied in future work the CO 2 /N 2 and CO 2 /CH 4 selectivity of such materials in dry and humid conditions